2015
DOI: 10.1080/15384047.2015.1095398
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of RAS screening before monoclonal antibodies therapy in metastatic colorectal cancer based on FIRE3 Study

Abstract: The surprising results published by FIRE-3 revealed that the overall survival (OS) of RAS wild-type metastatic colorectal cancer (mCRC) patients treated with Cetuximab(Cmab) and FOLFIRI combination was prolonged to 33.1 months. The substantial increase in testing and treatment costs, however, impose a considerable health burden on patients and society. Hence the study was aimed to assess the cost-effectiveness of RAS screening before monoclonal antibodies (mAbs) therapy based on FIRE-3 study. Four groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 29 publications
1
35
0
2
Order By: Relevance
“…Five studies showed cost-saving [ 41 45 ] compared to that of ‘no-testing’. Wen et al [ 32 ] evaluated cost-effectiveness of RAS screening prior to monoclonal antibodies and found that RAS testing before cetuximab is more cost-effective compared to KRAS-testing with cetuximab. After re-calculating their ICERs, we concluded that all strategies they used were well beyond the acceptable willingness to pay thresholds in China, but RAS testing appeared to be more favourable than KRAS testing for patients with mCRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies showed cost-saving [ 41 45 ] compared to that of ‘no-testing’. Wen et al [ 32 ] evaluated cost-effectiveness of RAS screening prior to monoclonal antibodies and found that RAS testing before cetuximab is more cost-effective compared to KRAS-testing with cetuximab. After re-calculating their ICERs, we concluded that all strategies they used were well beyond the acceptable willingness to pay thresholds in China, but RAS testing appeared to be more favourable than KRAS testing for patients with mCRC.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the cost-effectiveness of RAS testing and most of them found favourable results for RAS biomarker testing ( Table 2 ). Of these, two studies assessed the cost-effectiveness of RAS screening compared with that of KRAS testing with targeted therapies [ 32 , 36 ]. Both studies were performed from a Chinese health care system perspective and found that RAS testing was cost-effective compared to KRAS testing with cetuximab.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7]35 The best treatment decisions are driven by multiple factors, including drug costs, anticipated toxicities, and practice patterns, in addition to therapeutic effects. Recently, several studies in other countries have evaluated the cost-effectiveness of routine RAS screening in patients with mCRC [36][37][38] and Abbreviations: FOLFIRI, irinotecan, leucovorin, and fluorouracil; FOLFOX, oxaliplatin, leucovorin, and fluorouracil; ICER, incremental cost-effectiveness ratio; LY, life-year; QALY, quality-adjusted life-year; WTP, willingness-to-pay.…”
Section: Discussionmentioning
confidence: 99%
“…Однако данный вывод был сделан при сравнении результатов проспективных исследований эффективности добавления того или иного моноклонального антитела к химиотерапии без прямого проспективного сравнения эффективности моноклональных антител между собой [33]. В то же время при изолированном метастатическом поражении печени и «диком» типе гена KRAS в немецком исследовании цетуксимаб в комбинации с режимом FOLFIRI в 1-й линии оказался более эффективным по сравнению со схемой FOLFOX + бевацизумаб (ICER € 15 020 / LYG) [35].…”
Section: анти-Egfr-моноклональные антителаunclassified
“…• Авторы пришли к выводу, что комбинация цетуксимаба с химиотерапией при отсутствии мутаций в генах семейства RAS эффективнее сочетания с бевацизумабом не только клинически, но и экономически [35].…”
Section: анти-Egfr-моноклональные антителаunclassified